БЎЛАЖАК ЎКИТУВЧИЛАРДА РИТОРИКАНИ ЎРГАНИШГА ТАЙЁРГАРЛИГИНИНГ МУҲИМ ЖИҲАТЛАРИ - Пахратдинов, С.Ю. (SCIENCE and SOCIETY, 2023)
The rhetorical culture and the breadth of the spiritual world of the future teacher are important. The pedagogical activity of a teacher is continuous, serious attention should be paid to the systematic formation of a pedagogical rhetorical culture. The article reflects the special requirements of the future teacher for pedagogical rhetorical culture, ethics and manners, cordiality, secular etiquette.